Kali Linux intrusion and exploitation cookbook : over 70 recipes for system administrator or DevOps to master Kali Linux 2 and perform effective security assessment /: over 70 recipes for system administrator or DevOps to master Kali Linux 2 and perform effective security assessment. (2017) - Shah, Dhruv; Girdhar, Ishan
No abstract available